Hérésies - Peperstraete, Sylvie (2015)
What kinds of communities bring people together? How are they built? Where is unity, where is the multiplicity of humanity? Men can form separate, antagonistic, violently opposing communities. Is external division necessary to build internal cohesion? Nothing is more current than these questions.